Value of Heart Rate Variability, Neutrophil-Lymphocyte Ratio and Quality of Life of Patients with Depressive Symptoms in Acute Myocardial Infarction - Shatri, Hamzah; Adli, Mizanul; Muhadi, Muhadi; Abdullah, Murdani; Irawan, Cosphiadi; Putranto, Rudi; Koesnoe, Sukamto; Wijaya, Ika Prasetya (Jurnal Penyakit Dalam Indonesia, 2022)
Introduction. Major depression criteria can be found in more than 20% of coronary heart patients and more than 30% acute coronary syndrome patients have significant depressive symptoms. Several studies have shown that reduction of hearth rate variability (HRV) and enhancement of neutrophil lymphocyte ratio (NLR) can cause enhancement of morbidity and mortality in myocardial infarction patients. On the other hand, depression can cause reduction of HRV, enhancement of NLR and reduction of quality of life. This study aimed to determine differences in HRV, NLR and quality of life between acute myocardial infarction (AMI) patients with depressive symptoms and AMI patients without depressive symptoms. Methods. A cross-sectional study was conducted among AMI patients who were treated during the period of March to July 2021 at the Intensive Cardiac Care Unit (ICCU) Cipto Mangunkusumo Hospital Jakarta. Samples were taken consecutively until the amount of sample is met. Data were analyzed using unp aired T test. Results. There was a total of 46 subjects AMI patients in this study, ten subjects with depressive symptoms and 36 subjects without depressive symptoms. From the analysis, it was found that AMI patients with depressive symptoms had lower standard deviation normal to normal (SDNN) average (p=0.447), lower low frequency/high frequency (LF/HF) (p=0.323), and higher NLR average (p=0.438) than AMI patients without depressive symptom, although it was not statistically significant. Analysis showed that the mean value of SF36 total scores (p<0.001), physical function domain scores (p<0.001), energy domain scores (p<0.001), mental health domain scores (p<0.001), social function domain scores (p=0.028), bodily pain domain scores (p=0.002), and general health domain scores (p=0.002) were lower in AMI patients with depressive symptoms. Conclusion. AMI patients with depressive symptoms had lower SDNN, lower LF/HF, and higher NLR than AMI patients without depressive symptoms, although it was not statistically significant. AMI patients with depressive symptoms significantly have lower quality of life than AMI patients without depressive symptoms.